Out-Look on Worldwide Trends of Related Studies on Citrus Waste as Feed for Livestock Production: A Scientometric Analysis - Idamokoro, Emrobowansan Monday; Hosu, Yiseyon Sunday (Frontiers in Research Metrics and Analytics, 2022)
The present study aimed to reveal the abundant tapestry of research on citrus waste and livestock feed, taking into account the recurring challenge posed by feed shortage and high price of conventional animal feed in livestock farming. In total, 565 articles were retrieved in a BibTeX format for analysis using bibliometric package in R studio. The retrieved data included, but not restricted to authors, citations, key words, journals, institutions. Published outputs on citrus waste and animal feed for livestock production obtained from Scopus and web of science (WOS) data bases were used in this study. The field of citrus waste and livestock feed research experienced an increase in terms of research outputs with an annual growth of 10.20 % during the study period. Based on country level, Brazil was rated first with aggregate sum of publications (n = 81), with China having a huge global academic influence with most top article citations (n = 1338). The topmost authors’ keywords commonly used in the studied research area were citrus pulp (n=48), pectin (n=26), performance (n=22), citrus (n=33), which created a hint on associated studies on citrus waste and livestock feed. The present study provides a global trend to traverse the intellectual quandary on citrus waste and livestock feed research, and guidance for further studies in this field. It is essential to stress that the present study only dealt with core areas of citrus waste and livestock feed research, hence, it is anticipated that new empirical research and prospective solutions would afford new knowledge insight on citrus waste and livestock feed as new studies evolves.